Bosnia and Herzegovina : Labor Market Update, The Role of Industrial Relations - World Bank (Washington, DC, 2012)
This report identifies recent developments in the labor market in Bosnia and Herzegovina and by focusing on industrial relations, aims to provide new policy insights. The report shows that there have also been some improvements in labor market outcomes over the last few years. Nonetheless, changes in the legal and regulatory framework could contribute further to the performance of the labor market. High wages compared to productivity in the formal sector, the large and growing share of workers in the informal sector who are not covered by social insurance, and persistent unemployment are the three key labor market challenges facing Bosnia and Herzegovina (BH) today. Prospects for growth in Bosnia and Herzegovina are too fragile and not sustainable unless systemic reforms are introduced and effectively implemented. The report is organized as follows. The overview presents a summary of the findings and recommendations of the report, while Chapter 1 assesses the structure of and trends in the labor market. Chapter 2 examines the effects of the different wage determination processes on earnings, and Chapter 3 reviews the regulatory and industrial relations framework. A review of the international experience with collective bargaining is included in Annex V of this report and can serve as the basis for future discussions among local stakeholders about reform directions for collective bargaining.